User-Centered Prototype to Enhance E-Learning Engagement (EDUSHARE) - Muhammad Hafiz Shamsul Anuar; Abdulaziz Aborujilah (Journal of Computing Technologies and Creative Content, 2022)
Higher educational institutions’ structure has changed partially because of the introduction of technological initiatives. As a result, many universities in Malaysia have moved from a conventional approach to education to a more flexible approach for both lecturers and students. Many technological initiatives have already been implemented in universities in Malaysia. Many of them can be divided into two big categories, namely Massive Online Open Course (MOOC) and Learning Management System. Both of these mechanisms generally act as an initiative to assist the sharing and acquiring of academic content to students. In MOOCs, the engagement of learners to the material provided has become a big issue where research has shown that the completion rates of MOOCs can be as low as 7%, as the participation of learners seems to start to fall even after the first week of course attendance. Many attributes these low completion rates to lack of interaction or to the fact that completion is not vital, as learners usually search for a specific piece of information they need. MOOCs do not tailor academic content to each student’s unique needs, current understandings, and interests. Therefore, the aim of this project is to develop a hybrid application for the open access and management of online academic content. To achieve this aim, the methodology that is used for the development of this research project is the Waterfall model which includes phases of requirements, design, implementation, testing, and maintenance. As a proof of concept, the academic content related to the Information Technology (IT) domain area is selected. The system is developed mainly using Angular framework, Ionic, TypeScript, MySQL, HTML5, CSS3, and JavaScript. A study on the effectiveness of the system showed that the majority of the respondents agree that Edushare is a helpful supplementary for an education content sharing platform (83.33%) and helps tailor academic content according to the students’ needs (80%). The results indicate that this system has the potential to be a good supplementary for education content sharing platform for content personalized with the user’s needs.